2022
DOI: 10.1007/s12105-022-01504-y
|View full text |Cite
|
Sign up to set email alerts
|

Laminin Immunostaining in Biopsies as a Useful Biomarker of Early Invasion in Actinic Cheilitis and Differential Diagnosis Between Actinic Cheilitis and Lip Cancer: New Insights

Abstract: Background Squamous cell carcinoma of the lip (LSCC) and oral cavity can be life-threatening if not diagnosed early. Precancerous lesions like actinic cheilitis (AC), can transform into LSCC. Laminin is a fundamental component for basement membrane (BM) and its integrity may prevent neoplastic invasion. Therefore, laminin immunostaining of BM may be useful in identifying early invasion in actinic cheilitis and thus in the differential diagnosis between AC and invasive LSCC or high-grade epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, a significantly moderate positive correlation was observed between p53 and Ki-67 (Figure 4). HPV was detected in 26 (74.3%) patients, indicating the presence of one or two HPV genotypes (6,11,16,18). Additionally, 9 patients (25.7%) tested negative for HPV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a significantly moderate positive correlation was observed between p53 and Ki-67 (Figure 4). HPV was detected in 26 (74.3%) patients, indicating the presence of one or two HPV genotypes (6,11,16,18). Additionally, 9 patients (25.7%) tested negative for HPV.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported different rates of HPV infections in SNIP with and without dysplasia but without identifying any statistically significant relationship. Some studies were unable to detect HPV DNA in dysplasia and carcinoma associated with IP specimens, while others have shown varying HPV detection rates and contradictory results regarding the role of HPV infections in malignant and recurrent transformation [ 14 - 16 ]. Overall, the inconsistency in the results of previous studies may be attributed to factors such as DNA degradation in paraffin-embedded tissues, leading to false negative results, as well as geographical and racial differences.…”
Section: Discussionmentioning
confidence: 99%
“…Laminin-1 is in the Reichert membrane (extraembryonic basement membrane) [ 147 ]. A study by Vageli et al [ 148 ] assessed laminin immunostaining in biopsies as a useful biomarker of actinic cheilitis and differential diagnosis between actinic cheilitis and lip cancer. This marker can differentiate between low- and high-grade dysplasia.…”
Section: Discussion Of Potential Immunohistochemical Biomarkers In Gr...mentioning
confidence: 99%